(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article considers influence of historical novels of V.S. Pikul on the process of popularization of history among new generations. The author analyzes Pickle’s creative contributions to the genre of historical literature, revealing features of his works aimed at attracting attention of the modern audience. The article considers how the author uses artistic means to recreate historical events and characters, with the aim not only of entertainment, but also of educating a new generation of readers.